Computational Biology and Genome Informatics
Contains articles written by experts on a wide range of topics associated with the analysis and management of biological information at the molecular level. It contains chapters on RNA and protein structure analysis, DNA computing, sequence mapping, genome comparison, gene expression data mining, metabolic network modelling, and phyloinformatics. The important work of some representative researchers in bioinformatics is brought together for the first time in one volume. The topic is treated in depth and is related, where applicable, to other emerging technologies such as data mining and visualization.
Keywords: Computational biology. Genetics -Mathematical models. Genomics